Ubiquitylation in immune disorders and cancer: from molecular mechanisms to therapeutic implications - Simone Fulda; Krishnaraj Rajalingam; Ivan Dikic (EMBO Molecular Medicine)
Abstract Conjugation of ubiquitin to proteins (ubiquitylation) has emerged to be one of the most crucial post‐translational modifications controlling virtually all cellular processes. What was once regarded as a mere signal for protein degradation has turned out to be a major regulator of molecular signalling networks. Deregulation of ubiquitin signalling is closely associated with various human pathologies. Here, we summarize the current knowledge of ubiquitin signalling in immune deficiencies and cancer as well as the available therapeutic strategies targeting the ubiquitin system in combating these pathogenic conditions.